Prevalence of menopausal hot flashes in Lebanon: A cross-sectional study - Hala Ahmadieh; Nadia Jradi (Shahid Sadoughi University of Medical Sciences, 2021)
Abstract Background: Menopausal hot flashes or vasomotor symptoms are prevalent and could be debilitating in postmenopausal women. There is controversy regarding the risk factors for hot flashes, some of which may vary from one country or culture to another. Objective: To shed light on this matter by assessing the prevalence of hot flashes, their effect on quality of life, and their association with certain factors such as physical exercise, caffeine, spicy food consumption, dietary intake, smoking, alcohol, etc. Materials and Methods: A large cross-sectional study was conducted among 627 Lebanese women, aged 45-67 yr using a well-developed and comprehensive questionnaire, in order to better assess the prevalence of hot flashes, focusing on their characteristics, association with various factors, severity, and effect on the women's quality of life. Results: 62.5% of participants experienced hot flashes. A statistically significant difference was noted between women who experience hot flashes and their counterparts with respect to smoking, body mass index, spicy food consumption, education level, age, menstrual status, and parity. An association was not found with physical activity or other dietary factors. Conclusion: As an alternative for hormone therapy, clinicians should consider lifestyle changes to help manage hot flashes, which impose a tremendous physical and social toll on the women experiencing them.